Traditions and Customs of the Indian Armed Forces : Revised and Enlarged Edition - Das, Chand N., (Brill | Manohar Publishers & Distributors, 2021)
The cohesion and the spirit-de-corps in the Indian Armed Forces (Army, Navy and the Air Force) is fostered by various customs and traditions, which are reflected in the daily lives of their officers and men. They are not always legally binding but they are nonetheless followed willingly without coercion. There are traditions handed down from the past - Valour, Honour and Never to Surrender - that are intrinsic and resonate the lives of servicemen and image of their regiments and formations. On the other hand there are customs and traditions that regulate the lives of soldiers, sailors and airmen on a daily basis; military courtesies, dress and mess customs, regimental traditions, ceremonial drills and parades and the like. The various facets of customs and traditions of the armed forces were originally compiled by late Maj Gen Chand N. Das. The present volume has been inspired by the original and contains edited updated and enlarged facets that have been arranged in seven parts containing 33 chapters. Each chapter deals with different aspects of customs and traditions, viz., flags, colours and emblem, military uniform and dress customs, commemorative days, state and military funerals, battle honours, war memorials, medals and ribbons and so on.